Analisis Rasio Likuiditas, Solvabilitas, Dan Profitabilitas Terhadap Harga Saham Dengan Earning Per Share (EPS) Sebagai Variabel Moderasi - Rinofah, Risal; Sari, Pristin Prima; Sari, Novita (Universitas Gorontalo, 2022)
This study aims to analyze the effect of liquidity, solvency, and profitability on stock price with Earning Per Share (EPS) as a moderation variable. The population of this research is Food and Bavarage subsector companies which is listed in Indonesian Stock Exchange period 2016-2020. The method in this study used quantitative approach. The sampling technique used was purposive sampling based on certain criteria. The research sample was obtained through purposive sampling method and resulted in 16 companies so that the sample of this study was 80 sample which became the object of research. The analytical methods used in this research are descriptive statistics, the classic assumption test, F test, t test, multiple regression analysis, and residual test for moderating variable. The result showed that partially profitability ratio have significant effect on stock price. Meanwhile liquidity and solvency ratio does not have significant effect on stock price. Simultaneously, CR, DER, and ROA affected on stock price.Â The result from residual test showed that Earning Per Share (EPS) unable to moderate CR, DER, and ROA on stock prices.